Religion as Development Capital: A Discourse Analysis of State Construction in the Cikande Halal Industrial Zone Project - Ikhsan Ahmad; Rohmanur Aziz; Yusuf Zainal Abidin; Aep Kusnawan (Jurnal Iman dan Spiritualitas, 2026)
This study examines how the Government of Banten Province constructs and deploys halal discourse in the Cikande Halal Industrial Zone (KIHC) through official press releases, social media content, and promotional materials produced between 2019 and 2024. The research focuses on key concepts such as the commodification of religion, state hegemony, and the political economy of the halal sector. Using Norman Fairclough’s Critical Discourse Analysis, the study investigates linguistic strategies at the textual level, the mechanisms of production and circulation at the discursive practice level, and the broader power relations at the social practice level. The object of analysis includes institutional texts officially issued by the provincial government regarding KIHC. The findings reveal that the state systematically mobilizes religious lexicon and metaphors—such as “halal,” “syariah,” and “qibla”—to naturalize the fusion of religious morality and economic development agendas. The main challenge of the research is its exclusive reliance on state-produced narratives, which limits the ability to capture contesting voices. The study recommends greater public scrutiny of halal policy discourse and a more inclusive approach to community engagement in halal industrial development. In practice, this research demonstrates how religious language can serve as a tool for political and economic legitimation. This study advances the literature on the commodification of religion and the halal political economy by showing that halal discourse functions as a form of governmentality, merging moral authority with market logic to shape new forms of Muslim subjectivity within Islamic capitalism.